Analisis Kinerja Sistem Distribusi Energi Listrik dan Optimalisasi Beban Berbasis Pengukuran Lapangan - Suryadi, Fransiskus Xaverius; Lisapaly, Leonard; Sinambela, Rismen; Saputra, Tri Hannanto (Infotekmesin, 2026)
This study analyzes the performance of an electrical energy distribution system and load optimization in a low-voltage distribution network with dynamic load characteristics. Common problems in such systems include phase load imbalance, power losses, and power quality issues that may reduce operational efficiency. Previous studies have mainly focused on utility networks or conventional industrial installations, resulting in limited measurement-based evaluations at the institutional scale. This research aims to assess distribution system performance through direct field measurements, identify phase-current imbalance, evaluate power quality, and formulate load-optimization strategies. Measurements were conducted using a power quality analyzer under normal operating conditions for 30 minutes with a 1-minute recording interval. The results indicate that the distribution transformer operates at an average loading level of 47.4%, with a phase current imbalance of 14.89%, active power losses of 532.5 W, and an average power factor of 0.94. Overall, the findings show that improving load management and power quality plays a more significant role in enhancing system performance than increasing equipment capacity.